Bullwhip Effect of a Closed Leep Supply Chain with and Without Information Sharing of Customer Demand - (:unkn) unknown (My University, 2020)
In recent years, companies have become interested in a closed-loop supply chain that is concerned with the recovery pipeline. The expenses of a company can be influenced by large inventories and backlogs due to the bullwhip effect in the supply chain. Previous literature has shown that the bullwhip effect can be decreased by a reverse supply chain. This paper develops a closed-loop supply chain including seven echelons for recovery of end-of-life products. The model considers the order-up-to inventory policy and the exponential smoothing forecasting with a trend method in the system to assist in determining the ordering quantities. The best of the best is the method for this paper to choose a good smoothing parameter and to compare the necessity for information sharing. This test method provides the minimizing cost for the companies and analyzes the type of costs that can be reduced by selecting a good parameter value or utilizing information sharing. Furthermore, it also provides a way to reduce the bullwhip effect and verifies that the bullwhip index and cost are a complement to each other.
Keywords: bullwhip effect; closed-loop supply chain; information sharing; optimization